Training load differentiating training volume and training dose - Passfield, L.; Murias, J. M.; Sacchetti, M.; Nicolò, A. (International Journal of Sports Physiology and Performance, 2022)
We would like to thank our colleagues who have written to comment1,2 on our recent review about the validity of the training load (TL) concept,3 particularly given their extensive previous scientific and practical contributions on this topic. We are pleased to have the opportunity to extend discussion of the topic further in this reply. We suspect that how TL is conceptualized may lead to important differences in perspective as we find ourselves in broad agreement with several of the points raised in both letters. Therefore, we will respond by briefly outlining our interpretation of the TL concept and the rationale for linking this to an acute performance decrement (APD) and then addressing some specific points that were raised.